(untitled) (مجلة العلوم الشاملة, 2025)
Bottled water is an important source of drinking water in many developed and developing countries, including Libya. One of the main public health concerns related to bottled water consumption is its low mineral content or the absence of essential minerals that are vital for human health. This study aimed to assess the chemical quality of selected bottled water brands available in Bin Ghasheer, Libya) Uno , Aquasila, Sultan). A range of water quality parameters was analyzed, including physical parameters (total dissolved solids (TDS)) and chemical parameters (calcium (Ca²⁺), and sulphate (SO₄²⁻)), using standard analytical procedures and compared with the standards set by the Libyan authorities as well as the World Health Organization (WHO) guideline. "The results revealed significant variations among the tested bottled water samples and identified certain inconsistencies in the information provided on the labels, emphasizing the need to strengthen regulatory oversight to ensure the accuracy and reliability of information available to consumer.